The Fall of Lehman Brothers: The Recession Way - Gaurav, Kunal (Indian Journal of Finance, 2010)
On September 15, 2008 the whole world was shocked after hearing the announcement of Lehman Brothers Holdings Inc. to file for bankruptcy, one of the largest bankruptcies ever known to US economy. The recession was on its peak and one of the world’s largest investment banker (Lehman Brothers) decided to opt for bankruptcy in order to protect its asset and maximize values. Lehman Brothers reported the loss of 3.9 billion along with fresh write - downs on mortgage assets in its third fiscal quarter of year 2008 . Lehman Brothers had assets of 639 billion at the end of May 2008. When it filed for bankruptcy protection, it also reported to have a debt of more than 613 billion. "This bankruptcy filing represented the end of a 158 year-old company that survived world wars, the Asian financial crisis and the collapse of hedge fund Long-Term Capital Management, but not the global credit crunch" . This bankruptcy also represented the painful end of the four decade old career of the CEO of Lehman Brothers Holding Inc. -Richard Fuld, who had been leading this investment bank successfully since a long period of time.